The evaluation of non-topological components in Berry phase and momentum relaxation time in a gapped 3D topological insulator. (26th August 2015) - Sengupta, Parijat; Klimeck, Gerhard; Bellotti, Enrico
Abstract The zero gap surface states of a 3D-topological insulator host Dirac fermions with spin locked to the momentum. The gap-less Dirac fermions exhibit electronic behaviour different from those predicted in conventional materials. While calculations based on a simple linear dispersion can account for observed experimental patterns, a more accurate description of the physics of these systems and a better agreement between experimental data theoretical results can be obtained by including higher order <?CDATA k ?> <?MML k→ ?><inline-graphic xlink:href="ark:/27927/pgj2j527fhq" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> terms in the Hamiltonian. In this work, in presence of a time reversal symmetry breaking external magnetic field and higher order warping term, alteration to the topologically ordained Berry phase of <?CDATA (2n+1)π ?> <?MML (2n+1)π ?><inline-graphic xlink:href="ark:/27927/pgj2j527fg5" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />, momentum relaxation time, and the magneto-conductivity tensors is established. The relation between scattering times and the deviations to topological Berry phase of <?CDATA π ?> <?MML π ?><inline-graphic xlink:href="ark:/27927/pgj2j527fbz" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> is also emphasized.